Estrogen Deficiency and the Origin of Obesity during Menopause - Lizcano, Fernando (Hindawi Publishing Corporation, 2014)
Sex hormones strongly influence body fat distribution and adipocyte differentiation. Estrogens and testosterone differentially affect adipocyte physiology, but the importance of estrogens in the development of metabolic diseases during menopause is disputed. Estrogens and estrogen receptors regulate various aspects of glucose and lipid metabolism. Disturbances of this metabolic signal lead to the development of metabolic syndrome and a higher cardiovascular risk in women. The absence of estrogens is a clue factor in the onset of cardiovascular disease during the menopausal period, which is characterized by lipid profile variations and predominant abdominal fat accumulation. However, influence of the absence of these hormones and its relationship to higher obesity in women during menopause are not clear. This systematic review discusses of the role of estrogens and estrogen receptors in adipocyte differentiation, and its control by the central nervous systemn and the possible role of estrogen-like compounds and endocrine disruptors chemicals are discussed. Finally, the interaction between the decrease in estrogen secretion and the prevalence of obesity in menopausal women is examined. We will consider if the absence of estrogens have a significant effect of obesity in menopausal women.